Changing face of healthcare: digital therapeutics in the management of diabetes. (2nd December 2021) - Ramakrishnan, Priyadharshini; Yan, Kevin; Balijepalli, Chakrapani; Druyts, Eric
Abstract: Diagnosis, prevention, management and treatment of acute and chronic medical conditions have improved with technological advancements in terms of scalability, efficacy, access, and personalized approach. Digital therapeutic applications (DTx) (Blue Star, Diabeo System, Livongo Diabetes Program, Tidepool etc., ) use web-based applications/cloud platforms to provide evidence-based, personalized, rapid point of care management of chronic, behavior-modifiable conditions, including diabetes mellitus (DM). DTx has improved patient compliance, therapeutic success and economic outcomes in DM management by enabling active patient engagement, lifestyle change, comprehensive medical care, and periodic monitoring of glycemic status. Addressing concerns along DTx data vulnerability, comparative efficacy with conventional treatments, ability to accommodate diverse population needs, and resolving ambiguous regulatory policies and reimbursement guidelines are critical for increasing access to DTx, and overcoming availability, accessibility, and affordability issues in the existing resource limited healthcare environment. In this commentary the authors explore the potential, prospects, and challenges of DTx in the management of Diabetes Mellitus.